§ 1.

      6. , 0 = f(x).

6.01.

 f(x) = 26 4x5 3x3 4x2 + 2x + 2, x0 = 4;

6.02.

 f(x) = 36 8x5 7x3 + 4x2 + 3x + 6, x0 = 3;

6.03.

 f(x) = 35 2x4 + x3 x2 + x 585, x0 = 3;

6.04.

 f(x) = 26 x5 + 3x4 2x3 x2 + 3 + 42, x0 = 4;

6.05.

 f(x) = 36 4x5 + 5x3 + x 4, x0 = 2;

6.06.

 f(x) = 25 x4 + ix3 + (3 2i)x2 + 6 + 4i, x0 = 2i;

6.07.

 f(x) = 35 + x4 2x2 + x 106, x0 = 2;

6.08.

 f(x) = 26 22x5 + 87x4 133x3 + 9x2 + 135x 54, x0 = 3;

6.09.

 f(x) = 26 3x5 + x4 2x3 + 4x2 8x + 6, x0 = 1;

6. 10.

 f(x) = 6 4x5 2x4 + 2x3 + 8x 5, x0 = 1;

6.11.

 f(x) = 56 7x5 6x4 + x3 3x2 + 3x 2, x0 = 2;

6.12.

 f(x) = 36 2x5 + 8x4 2x3 + 2x2 7x + 6, x0 = 1;

6.13.

 f(x) = 6 2x5 15x4 + 18x3 + 46x2 27x + 12, x0 = 4;

6.14.

 f(x) = 6 2x5 6x4 + 16x3 3x2 4x 2, x0 = 2;

6.15.

 f(x) = 6 5x5 + 10x4 4x3 + 14x2 + 28x 20, x0 = 2;

6.16.

 f(x) = 6 5x5 + 3x4 2x3 + 4x2 + x + 46, x0 = 2;

6.17.

 f(x) = 6 5x5 + 6x4 + 2x3 7x2 6x 9, x0 = 3;

6.18.

 f(x) = 26 + 3x5 11x4 11x3 + 19x2 12x 12, x0 = 2;

6.19.

 f(x) = 6 2x5 + 3x3 12x2 + 2x 1, x0 = 2;

6.20.

 f(x) = 6 + 2x5 2x4 + 3x3 + 8x2 11x + 2, x0 = 2;

6.21.

 f(x) = 6 + 4x5 2x4 5x3 + 8x2 11x + 15, x0 = 3;

6.22.

 f(x) = 6 14x5 + 72x4 188x3 + 464x2 1344x + 1792, x0 = 4;

6.23.

 f(x) = 6 + 3x5 2x3 6x2 + 3x + 9, x0 = 3;

6.24.

 f(x) = 6 + 2x5 + x4 + 3x3 x2 + x 166, x0 = 2;

6.25.

 f(x) = 2x5 + 3x4 + x3 2x2 3x 1, x0 = 1;

6.26.

 f(x) = x5 2x4 + 3x3 6x2 + 2x 4, x0 = 2;

6.27.

 f(x) = 2x5 4x4 + x3 2x2 x 2, x0 = 2;

6.28.

 f(x) = x5 3x4 2x3 + 6x2 x + 3, x0 = 3;

6.29.

 f(x) = 6 2x5 + 3x3 x2 5x 300, x0 = 3;

6.30.

 f(x) = 6x4 + 19x3 7x2 26x + 12, x0 = 3;

6.31.

 f(x) = 2x5 + x4 11x3  + 7x2 13x + 6, x0 = 2;

6.32.

 f(x) = 2x5 + x4 x3 + 4x2 10x + 4, x0 = 2;

6.33.

 f(x) = 2x5 5x4 10x3 2x2 28x + 16, x0 = 4;

6.34.

 f(x) = 3x5 x4 24x3 + 8x2 27x + 9, x0 = 3;

6.35.

 f(x) = 5x5 x4 25x3 + 5x2 + 20x 4, x0 = 2;

6.36.

 f(x) = 2x5 + x4 10x3 5x2 + 8x + 4, x0 = 1.

\..\

                              Copyright © 2008-2009 ..   . .